Literature study on the evaluation of lead apron thickness in radiology service units - Edward, Sharon Gracia (Indonesian Physics Communication, 2025)
Radiation protection is an effort that can be undertaken to reduce the dangers of radiation. The ALARA principle of radiation protection is needed to minimize the radiation exposure received by workers based on three components: exposure time, distance, and the use of protective equipment. Therefore, an analysis of the effectiveness of lead aprons in protecting workers from radiation exposure is conducted. The method employed involves conducting a literature review on three journals discussing the effectiveness of lead aprons in protecting workers from radiation exposure based on varying apron thicknesses and exposure factors. At 100 kVp tube voltage, a lead apron with 0.25 mmPb thickness and exposure time of 100 mAs has an effectiveness of 25% (15 years old) and 98.1% (3 years old), while a thickness of 0.35 mmPb with an exposure time of 5 mAs has an effectiveness of 93%. At 70 kVp tube voltage, a lead apron of 0.35 mmPb thickness with an exposure time of 5 mAs has an effectiveness of 98.4%. A 0.5 mmPb lead apron with exposure times ranging from 20 mAs to 72 mAs has an effectiveness between 93.75% and 99.219%. The effectiveness of a lead apron is influenced by tube voltage, exposure time, age, and quality of the lead apron. A thick apron does not necessarily have high effectiveness in protecting workers if it has poor quality, and vice versa.